Study of Cerebrovascular Disease at Dhulikhel Hospital - Pokharel, Babu Ram; Pant, P; Gurung, R; Koju, R; Bedi, TRS; Pathak, M (Nepalese Heart Journal, 2013)
A stroke is the rapidly developing loss of brain function due to disturbance in the blood supply to the brain. It is a medical emergency that requires rapid diagnosis and treatment. The availability of CT Scan has made it easier for early diagnosis and intervention. The aim of this study was to identify the risk factors (eg. hypertension, diabetes mellitus and cigarette smoking) commonly seen in patients admitted in the hospital with stroke along with age group, sex distribution, duration of stay in the hospital and the occupancy of stroke patients admitted in medical ward. A total of 51 stroke patient were admitted in medical ward in the review period. CT scan was used to differentiate hemorrhagic from ischemic stroke. Patients were analyzed in terms of risk factors (like hypertension, diabetes mellitus and cigarette smoking) along with age and sex. In case of ischemic stroke along with CT Scan, ECG, Echocardiography, Carotid Doppler was done accordingly. Out of 2307 total admissions in medical ward, 51 cases (2.2%) were stroke patients. Among the stroke cases, 59% constituted male and 41% female. Similarly around 25% of the total cases were Diabetic / Hypertensive both or alone, 35% of the total cases were smokers, 48.6% of the cases were in the 51-70 age groups. 61% stayed in the hospital for 5 days or less. Cerebrovascular disease carries a lot of financial, physical, social and emotional implications. If we can address the modifiable risk factors, we can reduce the incidence of stroke. Nepalese Heart Journal | Volume 7 | No.1 | November 2010 (special issue) | Page 40-43 DOI: http://dx.doi.org/10.3126/njh.v7i1.8501